A qualitative approach of interactions between the domains of the International Classification of Functionality, Disability, and Health - Lima, Alexandra de; Viegas, Carina Souza; Paula, Maria Elizarda Machado de; Silva, Fabiana Caetano Martins; Sampaio, Rosana Ferreira (Acta Fisiátrica, 2010)
The International Classification of Functionality, Disability, and Health (ICF) is based on the bio-psycho-social model and enables understanding of the processes of functionality and disability through the interaction of its components. The aim of this study was to analyze the interrelationships between the domains of the ICF, describing the process of functionality and disability from the perspective of the individual. A qualitative approach was used with interviews and a life grid, built out of ICF domains, applied to 11 patients, and followed by filling in a diary of weekly activities. Most respondents made use of products and technologies such as canes, prostheses, or orthoses, and they had no difficulty in acquiring them through the SUS system. Personal factors that stood out were the ways of coping with new health conditions and new meaning in their lives. During the interviews, the importance of social support, particularly that offered by family and friends, the barriers encountered in the use of public transport, in addition to access of health care and Social Security benefits were prominent. Developing day-to-day strategies was a topic that showed how respondents reorganized their lives to minimize the difficulties they experienced. The data analysis from the interviews confirmed the existence of interaction between the components of ICF. This model was shown to be an important tool for understanding the process of human functionality and disability from the standpoint of the patient’s subjectivity and individuality, as well as for developing interventions and guiding public policy and health research.